Factores individuales mantenedores de las relaciones de pareja tóxicas (2022)
The objective of this research was to establish the individual factors that cause a group of men and women to maintain a toxic relationship. This work was carried out under the systemic theoretical approach, through the descriptive qualitative methodology. The analysis and subsequent discussion of the results was carried out in relation to the categories that emerge from the theoretical framework, which are Family, Peers, Sociocommunity, Jealousy, Difficulty in resolving conflicts, Insecure attachment, Deficit of communication skills, Low self-esteem and Relational history; as the only way to answer the research question posed and the objectives proposed in this research